Palladium-catalyzed diastereoselective synthesis of homoaldol equivalent products. Issue 22 (31st May 2017) - Horino, Yoshikazu; Sugata, Miki; Sugita, Tetsu; Aimono, Ataru; Abe, Hitoshi
Graphical abstract: Highlights: Homoaldol equivalent products can be synthesized with high diastereoselectivity. Pd complex promotes isomerization of 1-alkenylboronates to generate allylboronates. Reaction involves allylboration of aldehydes with α-acetoxy allylboronates. Abstract: A palladium-catalyzed reaction of easily accessible 3-(pinacolatoboryl)allyl acetates and aldehydes provides facile access to synthetically useful homoaldol equivalent products with high diastereoselectivity. The reaction presumably proceeds via allylation of aldehydes with α-acetoxy allylboronates that produced in situ by reductive elimination from allylic gem -palladium/boryl intermediates.